Innovation of feed additive for broiler chickens: A combination of ground corn and ginger (Zingiber officinale) as an immunostimulator and antivirus agent for avian influenza - Firda, Adelia Nihla; Ula, Kholifatul; Rahid, Waiel; Soepriandono, Hari (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Indonesia, with the fourth largest population globally, faces increasing demand for animal protein, particularly from broiler chicken production. However, this industry is challenged by the avian influenza virus, which causes high mortality in both poultry and humans. The virus’s hemagglutinin (HA) and neuraminidase (NA) glycoproteins are key to its infectivity. Innovative feed formulations that reduce viral titers while maintaining nutritional value are critical. This study aims to develop an innovative broiler chicken feed combining corn and bioactive compounds from ginger (Zingiber officinale) to inhibit avian influenza virus activity and sustain poultry health. Methods: This study employed a descriptive-experimental approach to develop an innovative broiler feed made from ground corn and ginger (JAZI) and to evaluate its effects on physiology, immunity, and growth. The work included research trend related, research manufacturing stage, and implementation stage to assess its practical effectiveness in enhancing broiler productivity and resilience against avian influenza. Findings: Ginger bioactives demonstrated the ability to inactivate viral particles by penetrating the lipid membrane, reducing HA activity, and preventing hemagglutination. Additionally, ginger supplementation was shown to enhance immune responses through activation of T-helper cells and antibody production, improving broiler performance indicators such as feed conversion ratio (FCR) and overall health. The integration of JAZI feed contributes to reduced antibiotic dependence and promotes sustainable poultry farming practices. Conclusion: The JAZI feed innovation provides a natural, safe, and sustainable solution for enhancing broiler immunity against avian influenza through synergistic nutritional and antiviral mechanisms. Novelty/Originality of this article: This study introduces JAZI as a dual-function feed innovation that not only supplies essential nutrition but also acts as an immunostimulant and antiviral agent against avian influenza, aligning with the One Health and Sustainable Development Goals (SDGs 15) frameworks.